Penerapan Metode MDLC (Multimedia Development Life Cycle) Dalam Rancangan Animasi 3 Dimensi Short Animation “Dampak Kekerasan Fisik Pada Anak” - Varnando; Ahmad Syazili (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
As technology advances rapidly in many industries, one in the multimedia sector, such as animation, can be used to overcome this problem. Dissemination of information will be more attractive and user-friendly with the use of multimedia. Illustration of multimedia-based information technology is 3D (3 Dimension) animation. The creative sector of the animation business continues to grow. Autodesk Maya is a program created primarily for creating complex motions and animations with natural motion, but can also be used to create accurate simulations of certain events. Children are the most beautiful gifts that are born into the world. Children need a family and good environmental conditions to be able to support their optimal growth and development. Based on the data collected, there is still a lot of violence against children, due to the lack of public knowledge about what will happen to children if they experience physical violence. With the aim of producing a 3D animated video on the Impact of Physical Violence on Children. Therefore this study aims to produce a 3D short animation video about the impact of physical violence on children. And through this animated video that has been produced, it is hoped that the public will be more sensitive in the pattern of educating children which will have a negative impact on the development of children if they do not teach the right pattern of children, such as committing violence on children.